Does the dimension of the graft influence patient morbidity and root coverage outcomes? A randomized controlled clinical trial. (8th May 2014) - Zucchelli, Giovanni; Mounssif, Ilham; Mazzotti, Claudio; Montebugnoli, Lucio; Sangiorgi, Matteo; Mele, Monica; Stefanini, Martina
Abstract Aim Primary aim of this study was to evaluate if patient morbidity was improved by diminishing graft thickness and height; secondary objective was to evaluate if such graft modifications influence root coverage and aesthetic outcomes. Methods 60 Miller class I and II gingival recessions (GR) (≥3 mm in depth) were treated with the coronally advanced flap plus extraoral de‐epithelialized free gingival graft (FGG). In 30 randomly selected control GRs ("big graft group"), the FGG thickness was ≥2 mm and the height was equal to bone dehiscence (BD); in the other 30 test defects ("small graft group"), the thickness of the FGG was <2 mm and the height was 4 mm. The post‐operative patient morbidity was assessed 1 week after the surgery. The clinical and aesthetic evaluations were performed 1 year after the surgery. Results Lower analgesic assumption, better post‐operative course evaluations, better patient colour match scores and better periodontist aesthetic assessments were reported in the "small graft" group. No statistically significant differences were demonstrated between the two groups in terms of recession reduction, CRC and increase in KTH. Greater GT increase was obtained in the control‐treated sites. Conclusions Coronally advanced flap plus CTG of reduced thickness and height was associated with less patient morbidity, better aesthetic evaluations with no difference in RC outcomes.